Enhancing the durability of hydrocarbon-membrane-based polymer electrolyte water electrolysis using a radical scavenger-embedded interlocking interfacial layer. Issue 2 (15th December 2021) - Choi, Sungyu; Shin, Sang-Hun; Lee, Dong-Hyun; Doo, Gisu; Lee, Dong Wook; Hyun, Jonghyun; Lee, Jang Yong; Kim, Hee-Tak
Abstract : Cerium oxide-containing interlocking interfacial layer improved mechanical adhesion and chemical stability of the interface. For the first time as a hydrocarbon-based membrane, it operated stably for more than 500 hours. Abstract : Hydrocarbon membranes are an attractive alternative to Nafion membranes for use in proton exchange membrane water electrolysis (PEMWE) due to their low gas permeability and high proton conductivity. However, hydrocarbon membranes and Nafion-based catalyst layers are prone to delamination, not allowing long-term operation of hydrocarbon-membrane-based PEMWE. In the present study, we propose a radical-scavenger-embedded interlocking interfacial layer (IIL) that addresses this interfacial delamination issue. The ball-socket joint structure of the IIL leads to mechanical interlocking at the interface, and the presence of cerium oxide as a radical scavenger prevents the hydrothermal degradation of the IIL. Cerium oxide-containing IIL-based PEMWE subsequently operates for more than 500 h with lower polarization at a voltage increase rate of 48 μV h −1, which is much lower than that of state-of-the-art hydrocarbon-based PEMWE and is even lower than that of Nafion-based PEMWE (53 μV h −1 ). The long-term durability of a hydrocarbon-membrane-based PEMWE system, reported for the first time in the present study, represents an important milestone for the development of cost-effective PEMWE systems.